The relationship between slack resources and firms' exporting behavior - Ine Paeleman; Catherine Fuss; Tom Vanacker (National Bank of Belgium, 2013)
We use a unique longitudinal dataset that tracks the exporting behavior of Belgian manufacturing firms between 1997 and 2009. We ask how slack resources, including financial and human resource slack, influence firms' exporting behavior. Our findings suggest that both types of slack resources have an inverted U-shaped relationship with the decision to export. This implies that higher levels of slack resources positively influence the likelihood of firms exporting, but too much slack negatively influences this likelihood. After controlling for the decision to export, we find no significant relationship between slack resources and export intensity. Nevertheless, we do find an inverted U-shaped relationship between slack resources and export diversity. Overall, this study provides new insight into how different types of slack resources influence different aspects of firms' exporting behavior.
Keywords: F10; L20; O15; O16; 330; financial resources; human resources; slack and export; Industrie; Export; Betriebswirtschaftliches Ziel; Humanressourcen; Betriebliche Liquidität; Verhaltensökonomik; Belgien